How do plastids and mitochondria divide?. (22nd November 2018) - Yoshida, Yamato; Mogi, Yuko
Abstract : Plastids and mitochondria do not multiply de novo but though the division of pre-existing organelles. Here, we review the structural frameworks of the mechanisms of plastid and mitochondrial division. Then, we highlight fundamental issues that need to be resolved to reveal the underlying mechanisms of plastid and mitochondrial division. Abstract: Plastids and mitochondria are thought to have originated from free-living cyanobacterial and alpha-proteobacterial ancestors, respectively, via endosymbiosis. Their evolutionary origins dictate that these organelles do not multiply de novo but through the division of pre-existing plastids and mitochondria. Over the past three decades, studies have shown that plastid and mitochondrial division are performed by contractile ring-shaped structures, broadly termed the plastid and mitochondrial-division machineries. Interestingly, the division machineries are hybrid forms of the bacterial cell division system and eukaryotic membrane fission system. The structure and function of the plastid and mitochondrial-division machineries are similar to each other, implying that the division machineries evolved in parallel since their establishment in primitive eukaryotes. Compared with our knowledge of their structures, our understanding of the mechanical details of how these division machineries function is still quite limited. Here, we review and compare the structural frameworks of the plastid and mitochondrial-division machineries in both lower and higher eukaryotes. Then, we highlight fundamental issues that need to be resolved to reveal the underlying mechanisms of plastid and mitochondrial division. Finally, we highlight related studies that point to an exciting future for the field.